Investigating Cultural Aspects in Indian Organizations: Empirical Evidence - Pereira, Vijay (Springer, 2015)
The purpose of this edited collection is to analyse the cultural aspects of Indian organizations. As the world’s largest and most diverse democracy, Indian society can be best described as an amalgam of multiple cultures, value systems, socio-political and institutional orientations. This book offers a theoretical and empirical basis for understanding the evolving and changing nature of these aspects in Indian organizations.